2017
DOI: 10.2174/1570159x14666161227150250
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Optic Nerve Axon Regeneration

Abstract: Background: Traumatic optic nerve injury is a leading cause of irreversible blindness across the world and causes progressive visual impairment attributed to the dysfunction and death of retinal ganglion cells (RGCs). To date, neither pharmacological nor surgical interventions are sufficient to halt or reverse the progress of visual loss. Axon regeneration is critical for functional recovery of vision following optic nerve injury. After optic nerve injury, RGC axons usually fail to regrow and die, leading to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 159 publications
(228 reference statements)
1
31
0
2
Order By: Relevance
“…In more detail, it has been shown that BDNF enhances RGC survival post-injury (Chen & Weber, 2001). Moreover, when BDNF is overexpressed specifically in the retinal tissue, the SMI-32+ large soma RGCs survival is promoted since these cells are more vulnerable to acute injury post-ONC (Feng et al, 2017). Finally, the combination of BDNF and the free radical scavenger S-PBN in a rat model of ON transection, showed an increase in RGC survival but not an improvement in long-distance axon regeneration.…”
Section: Novel Treatment Optionsmentioning
confidence: 98%
See 1 more Smart Citation
“…In more detail, it has been shown that BDNF enhances RGC survival post-injury (Chen & Weber, 2001). Moreover, when BDNF is overexpressed specifically in the retinal tissue, the SMI-32+ large soma RGCs survival is promoted since these cells are more vulnerable to acute injury post-ONC (Feng et al, 2017). Finally, the combination of BDNF and the free radical scavenger S-PBN in a rat model of ON transection, showed an increase in RGC survival but not an improvement in long-distance axon regeneration.…”
Section: Novel Treatment Optionsmentioning
confidence: 98%
“…The ON transection/axotomy (Figure 1a1) (Magharious, D'Onofrio, & Koeberle, 2011;Solomon et al, 1996;Vidal-Sanz, Bray, Villegas-Perez, Thanos, & Aguayo, 1987;Villegas-Perez, Vidal-Sanz, Rasminsky, Bray, & Aguayo, 1993), ON crush (ONC, Figure 1a2) (Selles-Navarro, Ellezam, Fajardo, Latour, & McKerracher, 2001;Tang et al, 2011;Templeton & Geisert, 2012), and ocular blast injury ( Figure 1b) (Hines-Beard et al, 2012) are the three classical models used for many years by researchers to study retinal and ON injury. While the ONC model allows for the investigation of effects on both the survival of retinal ganglion cells (RGCs) and axon regeneration, the axotomy model results in extended (more than 90% between two weeks and one month) cell death in the retina (Li, Sun, Yang, Zhu, & Feng, 2017;Villegas-Perez et al, 1993); thus, it is mainly used as a model for RGC apoptosis and survival. Axotomy is a highly invasive model, while there are many different protocols to crush the ON based on the methodology used and timing variations.…”
Section: Ton Rodent Modelsmentioning
confidence: 99%
“…Researchers continuously talk about axon regeneration and we found another article (Li et al, 2017) published last year that provides an overview regarding potential strategies for axonal regeneration of RGCs and optic nerve repair; it focuses on the role of cytokines and their downstream signaling pathways involved in intrinsic growth program and the inhibitory environment together with axon guidance cues for correct axon guidance. A more complete understanding of the factors limiting axonal regeneration will provide a rational basis, which contributes to develop improved treatments for optic nerve regeneration.…”
Section: About Treatmentmentioning
confidence: 99%
“…A variety of diseases occur due to non functional axons within the optic nerve that result in loss of visual function. Traumatic optic nerve (ON) injury is the leading cause of irreversible visual impairment worldwide [7] . Optic nerve disorders severely impact vision in one or both eyes.…”
Section: Cell Replacement Therapy For Optic Nerve Disordersmentioning
confidence: 99%
“…Hydrated collagen and N-isopropylacrylamide copolymer-based ECMs are fabricated. These are used in replacement therapy to improve nerve function mainly regeneration of defective neurons [104] . Extracellular matrix (ECM) macromolecules replicate within tissue-engineered biosynthetic matrices and influence cellular properties and behavior.…”
Section: Tissue Bioengineeringmentioning
confidence: 99%